KINERJA KARYAWAN DITINJAU DARI ASPEK KEPEMINPINAN DAN LINGKUNGAN KERJA - Rahmiana Rahmiana; Ismaulina Ismaulina (Jurnal Ekonomi Syariah, Akuntansi dan Perbankan (JESKaPe), 2017)
This study aims to determine the effect of leadership and work environment on employee performance at PT. Bank Aceh Syariah Ocean Branch Lhokseumawe. This research is quantitative research. The population in this study were all employees at PT. Bank Aceh Syariah Ocean Branch Lhokseumawe. The sampling technique uses the total sampling method, namely sampling techniques as large as the existing population. Based on predetermined criteria obtained the number of population and a sample of 31 employees. The type of data used is primary data obtained from questionnaires to employees of PT Bank Aceh Syariah. The data analysis method used is multiple linear regression analysis. The results of this study indicate that leadership and work environment simultaneously have a significant effect on employee performance. While the results of the study explain that all variables influence partially on employee performance. In terms of leadership (X1) has a significant effect on employee performance. It is proven by the significant results of tcount of 2.642 and the work environment (X2) has a positive and significant effect on employee performance. It is proven by the significant results of tcount of 4.565.